Natural expression variation for the Arabidopsis MED20a mediator complex subunit influences quantitative resistance to Sclerotinia sclerotiorum - Underwood, William; Sharma Poudel, Roshan (Frontiers in Plant Science, 2025)
IntroductionThe necrotrophic fungus Sclerotinia sclerotiorum is a destructive plant pathogen that can infect a broad range of host plants, including many agriculturally important crop species. Resistance to S. sclerotiorum is partial and quantitative, controlled by many genes. The identities of genes influencing resistance and the molecular mechanisms governing defense against this pathogen are poorly understood. To improve understanding of resistance, we performed genome-wide association studies of Arabidopsis thaliana response to inoculation with two isolates of the pathogen differing in aggressiveness and sought to validate our results by identifying the causal gene at a single mapped locus.MethodsA total of 325 A. thaliana ecotypes were evaluated for resistance at two timepoints after inoculation with S. sclerotiorum isolate 1980 or BN325. Genome-wide association studies were carried out using two different models to identify loci associated with resistance. A. thaliana mutant lines were then evaluated for candidate genes at a single locus to identify the most likely candidate gene influencing resistance, and sequencing of the candidate gene and promoter region was performed to identify putative causal variants.Results and discussionGenome-wide association studies mapped 30 loci associated with resistance to S. sclerotiorum. Surprisingly, correlations for response to the two isolates among A. thaliana ecotypes were relatively weak and no overlapping loci were mapped for resistance to both isolates. A. thaliana med20a mutants impaired in a subunit of the transcriptional Mediator complex were more susceptible to S. sclerotiorum and a single variant upstream of the MED20a gene was associated with resistance. These results improve our mechanistic understanding of resistance to this important plant pathogen.